From Josephus to Yosippon and beyond text - re-interpretations - afterlives - Bay, Carson 1986-; Aviʿoz, Mikhaʾel 1967-; Henten, Jan Willem van 1955- (Leiden Boston Brill, 2024)
This volume marks the state-of-the-art concerning research on Flavius Josephus, Sefer Yosippon, and reception history of both. The essays contained herein draw together and build upon past research to establish a new foundation for future work on these important texts.
"Two millennia ago, the Jewish priest-turned-general Flavius Josephus, captured by the emperor Vespasian in the middle of the Roman-Jewish War (66-70 CE), spent the last several decades of his life in Rome writing several historiographical works in Greek. Josephus was eagerly read and used by Christian thinkers, but eventually his writings became the basis for the early-10th century Hebrew text called Sefer Yosippon, reintegrating Josephus into the Jewish tradition. This volume marks the first edited collection to be dedicated to the study of Josephus, Yosippon, and their reception histories. Consisting of critical inquiries into one or both of these texts and their afterlives, the essays in this volume pave the way for future research on the Josephan tradition in Greek, Latin, Hebrew, and beyond"--
Description based on publisher supplied metadata and other sources
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Josephus, Flavius; Josippon -- Criticism, interpretation, etc; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D; Rome -- History -- Flavians, 69-96; Aufsatzsammlung